Effectiveness of theory-based breast self-examination intervention for breast cancer prevention among female college teachers in Pakistan: a cluster randomized controlled trial study protocol - Mahar, Benazir; Osman, Malina; Ahmad Fauzi, Fatimah (Public Library of Science, 2025)
Background: Breast cancer poses a significant health challenge in Pakistan, with a disproportionately high number of cases diagnosed at advanced stages. Despite the rising incidence, preventative measures like regular screening remain not commonly practiced among Pakistani women. While extensive research exists on breast cancer globally, there is a critical gap in studies specifically designed and evaluated to enhance breast self-examination practices within the Pakistani context.